2016
DOI: 10.1186/s12889-016-3376-3
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution, aeroallergens and admissions to pediatric emergency room for respiratory reasons in Turin, northwestern Italy

Abstract: BackgroundAir pollution can cause respiratory symptoms or exacerbate pre-existing respiratory diseases, especially in children. This study looked at the short-term association of air pollution concentrations with Emergency Room (ER) admissions for respiratory reasons in pediatric age (0–18 years).MethodsDaily number of ER admissions in a children’s Hospital, concentrations of urban-background PM2.5, NO2, O3 and total aeroallergens (Corylaceae, Cupressaceae, Gramineae, Urticaceae, Ambrosia, Betula) were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
33
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 42 publications
11
33
1
6
Order By: Relevance
“…Climate is associated with air pollution levels and may also act on the allergens by altering local and regional allergen production or by increasing the allergenicity of pollen (D'Amato et al 2016;Sénéchal et al 2015). Air pollution acts directly on pollen (D'Amato et al 2007), and particles carrying pollen allergen molecules are likely to play a role in the association between air pollution and respiratory allergic diseases (Bono et al 2016;Marchetti et al 2017). Finally, the level of pollen exposure is associated to allergic rhinitis incidence and prevalence and has also been associated to severity of rhinitis (Annesi-Maesano et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Climate is associated with air pollution levels and may also act on the allergens by altering local and regional allergen production or by increasing the allergenicity of pollen (D'Amato et al 2016;Sénéchal et al 2015). Air pollution acts directly on pollen (D'Amato et al 2007), and particles carrying pollen allergen molecules are likely to play a role in the association between air pollution and respiratory allergic diseases (Bono et al 2016;Marchetti et al 2017). Finally, the level of pollen exposure is associated to allergic rhinitis incidence and prevalence and has also been associated to severity of rhinitis (Annesi-Maesano et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing results on greenness and respiratory outcomes are still inconsistent [19][20][21]. Some authors reported a positive association between urban vegetation and asthma in children [22], speculating on non-urban vegetation as a potential source for allergens [23,24], which may negatively affect respiratory health. Moreover, living close to the forests has been associated with allergic symptoms [25,26] and greenness was differently associated to allergies, also depending on the study area [27].…”
Section: Introductionmentioning
confidence: 99%
“…e mechanism by which air pollutants contribute to the occurrence of diseases and premature death is not fully known. e in vivo and in vitro studies conducted so far showed that even exposing healthy volunteers to pollutant particles in the air for short periods triggers an inflammatory reaction on several different levels [34][35][36][37]. e immune system recognizes the antigens via toll-like receptors that are stimulated directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%